Modulation of Extracellular Matrix Activity, Neurotropic Factors and Sensory Innervation Associated Pain in Intervertebral Disc Degeneration using a Hyaluronic Acid Hydrogel. Issue 1 (April 2016) - Srivastava, Akshay; Abbah, Sunny A.; Carroll, Oliver; Tiernan, David; Owens, Peter; Dockery, Peter; Finn, David; Pandit, Abhay; Isa, Isma Liza Mohd
Introduction: Painful intervertebral disc (IVD) degeneration is mediated by inflammation, increase catabolic processes and neurotrophin production that sensitize innervation in the disc and leading to back pain. High molecular weight hyaluronic acid (HA) hydrogels demonstrate potential as bioactive materials for disc regeneration as they exhibit an anti-inflammatory effect, 1 reduce pain, 2 and mimic the native environment of the disc. 3 It is hypothesized that cellular HA/collagen hydrogels modulate extracellular matrix activity and neurotrophin expression in a 3D in vitro inflammation model and that acellular HA hydrogel inhibits in vivo hyper-innervation associated pain in an rat-tail injury model. Material and Methods: The density of 4 × 10 6 /ml inflamed nucleus pulposus (NP) was encapsulated in HA/collagen type II hydrogels during the synthesis. Hydrogels were incubated in media with/without IL-1β (10 ng/ml) until 3 day culture. Expression of NGF and BDNF, and the matrix component of aggrecan and collagen in NP cells were analyzed by qRT-PCR. All animal protocols were pre-approved by institutional Animal Care Research Ethics Committee (ACREC). Eight (8) Sprague Dawley rats were used in this study. The experimental group of sham (control), injury (untreated) and injury with acellular HA hydrogel implanted (treatment) were performed on disc Co4-Co5, Co5-Co6 and Co6-Co7. The coccygeal disc's of rat-tail were identified under an X-ray image intensifier and excising out 1 mm 3 size of AF tissue then induced injury. The rats were kept in recovery and assessing for nocifensive behaviors in response to thermal, cold and mechanical hyperalgesia/allodynia until 10 weeks post-operative. The rats were then sacrificed to harvest the discs and spinal cord so as to determine expression of GAP43, CGRP and c-fos for assessing sensory innervation and pain neuropeptide markers in the disc and dorsal horn of spinal cord respectively. Results: The collagen and aggrecan were up-regulated in the acute event of inflammation and down regulated as inflammation progressed in NP cells. Up-regulation of NGF and BDNF was evident in NP cells. Acellular HA hydrogel in the in vivo injury model revealed a significant decrease of sensory innervation in NP and AF tissue. Conclusion: The cellular 3D hydrogel platform mimics the native extracellular matrix of NP. The therapeutic effect of HA hydrogel was shown with down-regulation of neurotrophins and suppression of hyper-innervation in the inflammation and injury model respectively. Acknowledgments: Majlis Amanah Rakyat (MARA) Malaysia and AO Research Institute – Collaborative Research Program for providing financial support to this project. This publication has emanated from research supported in part by a research grant from Science Foundation Ireland (SFI) and is co-funded under the European Regional Development Fund under Grant Number 13/RC/2073. References Isa ILM, Srivastava A, Tiernan D, et al. Hyaluronic Acid Based Hydrogels Attenuate Inflammatory Receptors and Neurotrophins in Interleukin-1β Induced Inflammation Model of Nucleus Pulposus Cells. Biomacromolecules 2015;16(6):1714–1725 Caires R, Luis E, Taberner FJ, et al. Hyaluronan modulates TRPV1 channel opening, reducing peripheral nociceptor activity and pain. Nat Commun 2015;6:8095 Collin EC, Grad S, Zeugolis DI, et al. An injectable vehicle for nucleus pulposus cell-based therapy. Biomaterials 2011;32(11):2862–2870